Persecution and Escape - Sascha Becker; Volker Lindenthal; Sharun Mukand; Fabian Waldinger (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We study the role of professional networks in facilitating emigration of Jewish academics dismissed from their positions by the Nazi government. We use individual-level exogenous variation in the timing of dismissals to estimate causal eects. Academics with more ties to early émigrés (emigrated 1933-1934) were more likely to emigrate. Early émigrés functioned as "bridging nodes" that facilitated emigration to their own destination. We also provide evidence of decay in social ties over time and show that professional networks transmit information that is not publicly observable. Finally, we study the relative importance of three types (family, community, professional) of social networks.
Keywords: I20; I23; I28; J15; J24; N30; N34; N40; N44; 330; professional networks; high-skilled emigration; Nazi Germany; Jewish academics; universities